The Jesus quest : the third search for the Jew of Nazareth - Witherington, Ben, III (Downers Grove, Ill. InterVarsity Press, 1995)
"Who is the Jesus behind the Gospel narratives? How would he have been understood by his contemporaries? Did the church transform a charismatic rabbi or a peasant-philosopher into its heavenly, incarnate Lord? Does the key to Jesus' real identity actually lie in the Gospel of Thomas, the Gospel of Peter or other noncanonical Jesus literature suppressed by the ancient orthodox church? What do the sects, parties and movements of Jewish Palestine tell us about the real Jesus, his words, his actions and his intentions?" "These are the questions being asked by a new generation of investigators of the man behind the origin of Christianity. Dubbed the Third Quest of the historical Jesus, this renewed effort is a transformation of the first quest, memorialized and chronicled by Albert Schweitzer, and the second quest, carried out in the 1950s and 1960s in the wake of extreme Bultmannian skepticism. Now in the 1990s, with the time, place and social setting of Jesus newly illumined by renewed and vigorous investigation of the Dead Sea Scrolls and other Jewish and Hellenistic sources, there has appeared a surge of scholarly books on Jesus within his Jewish and Mediterranean environment." "The controversial works of John Dominic Crossan, Marcus Borg and Burton Mack, and the results of the Jesus Seminar have been thrust upon the public by publicists and media as the voices of learned consensus. Meanwhile, at the center of the scholarly investigation of Jesus, a less celebrated but certainly no less informed majority rejects many of the methods and conclusions of those who have captured the limelight."--Jacket.
Keywords: Jesus Christ -- Biography -- History and criticism. Bible. -- Gospels -- Criticism, interpretation, etc. -- History -- 20th century. Jesus Christ -- Historicity